Plasma Deposition of Parylene-like Films with Chemical Functional Groups for Immunoassays - Song, Zhiquan; Jung, Jaeyong; Kim, Tae-Hun; Park, Jun-Hee; Song, Hyun-Woo; Kang, Min-Jung; Kim, Moo-Hwan; Pyun, Jae-Chul (American Chemical Society, 2024)
Parylene-like films obtained via the plasma decomposition of parylene precursors with functional groups (amino and formyl) are proposed as an alternative to those obtained via the thermal method. To analyze the chemical functional groups after plasma deposition, a surface analysis of the parylene films using the two different deposition methods was performed via Fourier transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS). The FT-IR analysis revealed that the featured peaks of the chemical functional groups were maintained in the parylene-like films obtained via the plasma deposition method. The XPS analysis revealed that the featured chemical functional groups of parylene-AM and parylene-H were maintained after plasma deposition. The surface energy of the parylene films was estimated by using contact angle measurements. The plasma-deposited parylene films were then employed for protein immobilization via the functional groups using horseradish peroxidase (44 kDa) and green fluorescent protein (25 kDa) as model proteins. The parylene-AM and parylene-H films obtained via plasma deposition exhibited higher immobilization efficiencies than did the same parylene films obtained via thermal deposition. Finally, a competitive immunoassay was obtained by immobilizing the Fv-antibodies on plasma-deposited parylene-AM and parylene-H films via covalent bonding. Using heat-deactivated SARS-CoV-2 as a real sample, the limit of detection at the feasible level for the medical diagnosis of COVID-19 was achieved using a competitive immunoassay based on immobilized Fv-antibodies on plasma-deposited parylene films.